2014
DOI: 10.3390/ijms15034856
|View full text |Cite
|
Sign up to set email alerts
|

Dimers of G-Protein Coupled Receptors as Versatile Storage and Response Units

Abstract: The status and use of transmembrane, extracellular and intracellular domains in oligomerization of heptahelical G-protein coupled receptors (GPCRs) are reviewed and for transmembrane assemblies also supplemented by new experimental evidence. The transmembrane-linked GPCR oligomers typically have as the minimal unit an asymmetric ~180 kDa pentamer consisting of receptor homodimer or heterodimer and a G-protein αβγ subunit heterotrimer. With neuropeptide Y (NPY) receptors, this assembly is converted to ~90 kDa r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 86 publications
1
6
1
Order By: Relevance
“…However, the selective NPY1R antagonist BIBO3340 did not significantly decrease NPY1R-induced responses (Figure 2A). Recently, it has been reported that NPYR forms heterodimers with other GPCRs (41,42). In some cases, the responses of GPCR heterodimers were not notably inhibited by the antagonist of each GPCR monomer (43).…”
Section: Discussionmentioning
confidence: 99%
“…However, the selective NPY1R antagonist BIBO3340 did not significantly decrease NPY1R-induced responses (Figure 2A). Recently, it has been reported that NPYR forms heterodimers with other GPCRs (41,42). In some cases, the responses of GPCR heterodimers were not notably inhibited by the antagonist of each GPCR monomer (43).…”
Section: Discussionmentioning
confidence: 99%
“…Despite growing evidence for GPCR homo-and heterodimerization, the functional outcomes of these interactions remain elusive. Within the NPY receptor family, all receptors have been shown to form homodimers, while Y1R additionally can heterodimerize with Y5R, Y4R and β-adrenergic receptors (39)(40)(41)(42)(43)(44)(45)(46)(47). Nevertheless, reports pertaining to the receptor fate upon agonist stimulation vary depending on the methodology, while experiments with bivalent ligands do not support their enhanced ability to stimulate NPY receptors (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the goal of the current study was to characterize NPY receptor interactions in live cells, as well as the impact of these processes on the receptor activation and function. In contrast to previous studies using fluorescence and bioluminescence resonance energy transfer methods (FRET and BRET, respectively), as well as isolated membrane preparations, all of which analyzed the entire population of the receptors present in the cells, we have focused on their active fraction present on the plasma membrane and responsible for ligand binding (39)(40)(41)(42)(43)(44)(45)(46)(47). To elucidate the functional role of the receptor interactions, we used the mitogenic activity of NPY as a model, since previous results from our laboratory strongly implicated the role for the heterotypic NPY receptor expression in augmenting its growth-regulatory effects in various cells (29,37).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations